Validitas Media Pembelajaran Interaktif pada Materi Mengevaluasi Informasi dalam Teks Negosiasi untuk Siswa SMA - Hidayatullah, Al Abil; Ramadhanti, Dina (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study aims to test the validity of interactive learning media on material evaluating information in negotiation texts for high school students. Using a descriptive quantitative approach, the media developed based on needs analysis was assessed by three media experts and three subject matter experts through a questionnaire instrument. The results of the analysis show that the media obtained a very high validity score, with a percentage of 83.33% from media experts (covering aspects of design, interactivity, and accessibility) and 87.67% from subject matter experts (covering aspects of content suitability, presentation, and language). These findings confirm that the interactive media is feasible and valid for implementation in teaching negotiation texts at the high school level.